Efeito econômico do complexo industrial e portuário do Pecém sobre os municípios de Caucaia e São Gonçalo do Amarante: uma aplicação do método de controle sintético generalizado - Pessoa, Suely Rocha de Pinho (2020)
The work analyzes the economic impact of the public infrastructure on local economic growth. The generalized synthetic control method is used to measure the causal effect of the installation of the Complexo Industrial e Portuário do Pecém on the economic growth of the cities Caucaia and São Gonçalo do Amarante. The results point to a period of investment transition, exerting a positive effect on the per capita GDP of the cluster after 2006. The average effect of treatment on the treaties (ATT) presents an increasing time path, indicating a virtuous growth cycle. Auxiliary regressions suggest that the effect on the private side of the economy occurred via the industrial sector.